2023
DOI: 10.1186/s12953-023-00224-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of S100A8 in peripheral blood mononuclear cells from patients with depression treated with SSRIs: a pilot study

Concepción Gamboa-Sánchez,
Enrique Becerril-Villanueva,
Samantha Alvarez-Herrera
et al.

Abstract: Background Major depressive disorder (MDD) affects more than 350 million people worldwide, and there is currently no laboratory test to diagnose it. This pilot study aimed to identify potential biomarkers in peripheral blood mononuclear cells (PBMCs) from MDD patients. Methods We used tandem mass tagging coupled to synchronous precursor selection (mass spectrometry) to obtain the differential proteomic profile from a pool of PBMCs from MDD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis. A recent research suggested that EGR1 [99] and S100A8 [100] contributed to the advancement of depression and anxiety. ATF3 [101], S100A12 [102], CD163 [103] and S100A8 [104] could act as diagnosis and prognosis biomarker for airway inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…EGR1 [97], ATF3 [63] and XIST (X inactive specific transcript) [98] are involved in the development of osteoporosis. A recent research suggested that EGR1 [99] and S100A8 [100] contributed to the advancement of depression and anxiety. ATF3 [101], S100A12 [102], CD163 [103] and S100A8 [104] could act as diagnosis and prognosis biomarker for airway inflammation.…”
Section: Discussionmentioning
confidence: 99%